Word Formation in Female Version of the Name in the Dialects Bug (Linguostylistic Studies, 2015)
The article analyzes the creation of women's names prybuzhan variants that arose as a result of suffixation of complete and truncated basis of official names, truncation and truncated suffix-ways with their various combinations. In addition, derivatives revealed lexical creation.A womanish repertoire mostly coincides with zagal'noukrainskim nominal creation. At the same time, single variants which belong to the concrete transmitter of the name with the most various facilities of expression are fixed.For creation of deminutivnikh variants 23 suffixes which give the name a zdribnilo-pestliviy tint in a value are used: -as′-a, -echk-a, -ik, -ichk-a, -k-a, -on′k-à, -ul′-a, -shk-a  and others; 19 suffixes are with shrublet shade: -ar-a, -is′k-o, -ik-a, -op-a, -ut-a, -kh-a but other. Neutral in relation to the emotional colouring are variants of the names with suffixes -′à, -dz′-à, -in-a, -n′-à, -s′-à.Our material rotined that more frequent all the variants of the names of habitants of this territory are formed by a suffix and truncating with a suffix with different combinations. Not found out reduplikacii. Key words: womanish variants of the names, tender, increased shrub, neutral suffixes, productive types. References